Long-term investigation of spatial–temporal variations, risk assessments, and controlling factors of persistent organic pollutants (HCHs, DDTs, and PAHs) and heavy metals in coastal regions along the Chinese Bohai Sea - Su, Yanting; Wang, Wanguan; Su, Yueyue; Wang, Xiaoxuan; Zhao, Haitao; Li, Zhunjie; Yu, You (Frontiers in Marine Science, 2024)
Persistent organic pollutants (POPs) and heavy metals in marine systems have been given more and more attention due to their high toxicology and bioaccumulation capacity. After discharging into the marine systems, large proportion of POPs and heavy metals are likely to retain in coastal seas, causing serious contamination and high ecological risks. However, lacking of systematic studies restricts our understanding of POPs and heavy metals cycling in coastal regions. Herein, the coastal regions along the Chinese Bohai Sea (an important fishing and typically polluted area) was chosen, to establish a study model for investigating long-term spatial-temporal variations, risk assessments, and controlling factors of hexachlorocyclohexanes (HCHs), dichlorodiphenyltrichloroethanes (DDTs), polycyclic aromatic hydrocarbons (PAHs), and heavy metals in coastal region. The results showed that concentrations of HCHs, DDTs, and PAHs in sediment, and contents of heavy metals in seawater and sediment were higher than those in other coastal regions during 2015-2018, and concentrations of As and Cu in approximately 95% and 20% of sampled organisms exceeded maximum permissible levels recommended by China and WHO, respectively. The significantly temporal variations in HCHs and PAHs concentrations indicative of increasing POPs pollution, and no significantly temporal variations in most heavy metals concentrations were found. Meanwhile, the higher concentrations of POPs and heavy metals were mainly located at estuaries and other nearshore areas. The geo-accumulation index (Igeo), potential ecological risk index (PERI), and provisional tolerable daily intake (PTDI) showed that As, Cd and Hg should be listed as the primary heavy metals pollutants in sediment, and higher dietary risk was posed by As through seafood consumption, the dietary risks posed by HCHs, DDTs, and PAHs were relatively lower. Finally, the results of multiple regression, Pearson, and cluster analyses indicated that anthropogenic activities (e.g., industrial and agricultural discharges, riverine input) played important roles in controlling HCHs, DDTs, PAHs, and heavy metals distributions in coastal regions along the Chinese Bohai Sea. The outcomes of this study are expected to shed new light on an improved understanding of POPs and heavy metals cycling and provide a scientific basis for contamination control in coastal systems.